Analysis Of Innovation Of Aren Sugar Farmers Towards Economic Improvement In Cibaliung District, Pandeglang Regency - Roy Tumpal Pakpahan (SEAN Institute, 2024)
Pandeglang district located in Cibaliung district is a professional farmer and many have opened their own land by growing a variety of crop commodities, both seasonal and annual crops.One of the villages in the district of Pandeglang where most of the inhabitants are farmers is the Cibaliung district. One of the agricultural commodities used as a source of income in Cibaliung district is Aren. In this research, researchers used qualitative research methods to describe Innovation of Sugar Farmers Aren versus Improving the Economy of Cibaliun district. Data used in this research are primary data and secondary data. The researchers used triangulation to evaluate the validity of data The potential to be developed in Cibaliung Cabupatan Pandeglang is numerous enough and wide enough to be used as agricultural land. The size of the land that is owned by the sugar production of various kinds, there are more than 1 ha da tons also less than 1 Ha. And the size of land influences the number of aren trees that grow in the land. Innovation in marketing and production, can increase the income of the economy of the community. As well as innovation and good management is essential to increase the production and sale of sugar aren, which in turn can boost the society of Cibaliung district. Challenges faced by farmers include the availability of raw materials, skilled labor, and traditional means of production.